2004
DOI: 10.1104/pp.103.032102
|View full text |Cite
|
Sign up to set email alerts
|

A Nodule-Specific Dicarboxylate Transporter from Alder Is a Member of the Peptide Transporter Family

Abstract: Alder (Alnus glutinosa) and more than 200 angiosperms that encompass 24 genera are collectively called actinorhizal plants. These plants form a symbiotic relationship with the nitrogen-fixing actinomycete Frankia strain HFPArI3. The plants provide the bacteria with carbon sources in exchange for fixed nitrogen, but this metabolite exchange in actinorhizal nodules has not been well defined. We isolated an alder cDNA from a nodule cDNA library by differential screening with nodule versus root cDNA and found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 51 publications
1
69
0
1
Order By: Relevance
“…Around 1,500 unigenes (11%) for A. glutinosa and 2,000 unigenes (14%) for C. glauca were shown to be regulated or specifically induced during nodule development. In both species, it is worth noting that among the most highly induced genes (Table III), two previously characterized actinorhizal nodulins, a subtilase (Ag12/Cg12) and a dicarboxylate transporter (Agdcta1; Ribeiro et al, 1995;Laplaze et al, 2000;Svistoonoff et al, 2003;Jeong et al, 2004), were identified. More detailed data analysis enabled us to identify other known A. glutinosa nodulins with homologs in C. glauca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 1,500 unigenes (11%) for A. glutinosa and 2,000 unigenes (14%) for C. glauca were shown to be regulated or specifically induced during nodule development. In both species, it is worth noting that among the most highly induced genes (Table III), two previously characterized actinorhizal nodulins, a subtilase (Ag12/Cg12) and a dicarboxylate transporter (Agdcta1; Ribeiro et al, 1995;Laplaze et al, 2000;Svistoonoff et al, 2003;Jeong et al, 2004), were identified. More detailed data analysis enabled us to identify other known A. glutinosa nodulins with homologs in C. glauca.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a number of genes have been shown to be up-regulated in response to interaction with Frankia (Pawlowski, 2009). These genes include an enolase (van Ghelue et al, 1996), a subtilisin-like protease (Laplaze et al, 2000), a dicarboxylate transporter (Jeong et al, 2004), and nitrogen assimilation genes (Guan et al, 1996) as well as numerous poorly characterized genes.…”
mentioning
confidence: 99%
“…Recently, the Arabidopsis NPF7.3/NRT1.5 was shown to be a K + transporter and to NO 3 − -dependently control K + homeostasis in shoots (Drechsler et al 2015;Li et al 2017). Other family members, for example, function as a NO 3 − excretion transporter or in actinorhizal and rhizobial N-fixing symbioses (Jeong et al 2004;Segonzac et al 2007;Yendrek et al 2010), whereas a role of NPF proteins in plant-AMF interactions has not been observed yet.…”
Section: Introductionmentioning
confidence: 99%
“…NRT1(PTR) is a large family of transporters, comprising 53 members in Arabidopsis (Arabidopsis thaliana), 84 members in rice (Oryza sativa), with NRT1 (PTR) members known in several other species (Tsay et al, 2007;Zhao et al, 2010). In addition to transporting NO 3 2 coupled to H + movement, members of the NRT1(PTR) family have been found to transport dipeptides or tripeptides, amino acids (Waterworth and Bray, 2006), dicarboxylic acids (Jeong et al, 2004), auxin (Krouk et al, 2010b), and/or abscisic acid (Kanno et al, 2012). Only a small number of NRT1 (PTR) proteins have been functionally studied compared with the large number that exist in higher plants; thus, the number of biochemical functions ascribed to this family may expand.…”
mentioning
confidence: 99%